Milk fat globule epidermal growth factor 8 (MFG-E8): A novel protein in the mammalian endometrium with putative roles in implantation and placentation - Bocca, Silvina M. (2012)
MFG-E8 is a novel endometrial protein with conserved functions in tissue remodeling and angiogenesis in non-uterine tissues. Our aims were: 1. To examine the presence of MFG-E8 protein in the human endometrium during the window of implantation, in human endometrial cell lines, in human placental tissue at different gestational ages, and in murine implantation sites during early gestation; and 2. To study the regulation of MFG-E8 mRNA expression in mice implantation sites. Study design: MFG-E8 protein and its receptor integrin αvβ3 were detected by immunostaining in human endometrial biopsies obtained from normal volunteers, in human endometrial cell lines (epithelial: Ishikawa and HEC-1A, stromal: HESC, and endothelial: HEEC), in human products of conception from all trimesters of gestation, and in murine implantation and inter-implantation sites dissected on days 5 and 8 post-coitus. MFG-E8 gene expression was assessed by RT-PCR. Main outcome measures: Immunohistochemical determination of MFG-E8 in endometrium and products of conception as well as relative MFG-E8 mRNA expression in mice implantation sites. Results: MFG-E8 protein was present almost exclusively in the epithelial compartment of human endometrium. It was also expressed in the cytotrophoblasts and syncytiotrophoblasts outlining chorionic villi of the human placenta at all trimesters of gestation, and in murine implantation sites. MFG-E8 mRNA was significantly up-regulated in murine implantation sites and with increased gestational age. Conclusions: MFG-E8 expression in the endometrial epithelium as well as in chorionic villi suggests its possible role in endometrial reorganization during the receptive phase and in events related to normal pregnancy in mammals.